Managing effective reform for Community Medicine subject: Vision to actions - Kadri, Amiruddin (Indian Journal of Community Health, 2017)
Reforming Community Medicine discipline is the felt need amongst fraternities of Community Medicine but making effective change is the greatest challenge. It is uphill task and many big organizations failed in ushering the change without full thought to how to manage reform? With changing demand and role of the subject, Royal Colleges of Physicians of United Kingdom had tried to change Faculty of Public Health to Faculty of Community Medicine and then to Faculty of Public Health Medicine to manage the change but it failed (1). However, we need to learn from them and succeed in managing the change.